The Role of Therapy Education of Islamic Meaning to Overcome Todayâs Global Human Crisis - Aminah, Nina (International Journal of Nusantara Islam, 2015)
Modern community are exposed to current issues related to the very complex personality. Islam offers a therapeutic meaning to overcome the global human crisis through the holy Quâran. This study aims to provide a qualitative analysis of logotherapy alternative to global human who experience critical conditions such as the door of death (sakaratul maut), acute illnesses, HIV Aids, kidney illness, stroke, coma, depression / stress, due to the hazards, and other refractory disease. The study showed that the therapy of Islamic meaning based on the holy Qurâan is broader and more comprehensive than the meaning therapy by Viktor E. Frankl.